ORGANIZATIONAL AND METHODOLOGICAL BASIS OF THE DEVELOPMENT CIVIL ACTIVE STUDENTS - Xing, Zhefu (Educological discourse, 2016)
The article presents the essence of adaptation of foreign students to the structure of education in Ukrainian universities. The criteria, indicators, levels of adaptation of foreign students to study in Ukrainian universities. Arrange a system diagnostic tools to determine the level of adaptation of foreign students to study in Ukrainian universities.